Situation of labor codes in the structure of regulatory and legal acts of the Eurasian Economic Union member states - Alimkhanova, S.K. (Bulletin of the Karaganda University “Law Series”, 2020)
The article considers regulatory legal acts in the field of labor legislation of the Eurasian Economic Union member states. The purpose of the study is that on the basis of a comparative analysis of the national legislation of the Eurasian Economic Union member states to formulate a definition of the labor code, to determine the place of labor codes in the system of labor legislation of the designated states, as well as to develop proposals for improving the regulatory legal acts of a separate norm in the labor sphere of the Eurasian Economic Union member states. The studied methods were based on a comparative legal method and an analysis of labour legislation in member States of the Eurasian Economic Union. This article presents the results of comparison of the current labour legislation of the Republic of Kazakhstan, the Russian Federation, the Republic of Belarus, the Kyrgyz Republic and the Republic of Armenia with regard to the regulation of labour relations and summarizes the legal definitions of the term «code» in four of these five countries. As a result, the definition of the labor code was formed, problems of correlation between the labor code and other normative legal acts adopted in the countries-participants of the above-mentioned union were identified. The conclusion was drawn that there is no call from ion norms to the Labour Code and that the specific legal act should take precedence over all other laws.